The Role of the Principal in Shaping and Building the Character of the Santri at Madrasah Aliyah Badridduja from a Dramaturgical Perspective - Mohammad Irfan Efendi; Moh. Rifa'i (Institute of Computer Science (IOCS), 2022)
This study aims to determine: (1) the leadership role of the principal in shaping and building student character, (2) the implementation of character education in Madrasah Aliyah Badridduja, Kraksaan, Probolinggo, East Java, (3) the importance of character education in the modernization era. qualitative descriptive research. Data was collected by using observation, interview, and documentation techniques. Checking the validity of the data is done by: checking the data against information from interviews with observations and documentation. The results showed that the implementation of character education at Madrasah Aliyah Badridduja was carried out through: character education planning, character education implementation, character education assessment. The implementation of character education at Madrasah Aliyah Badridduja is carried out through synergy through the integration of character education with intracurricular and extracurricular activities.